A study on the effectiveness of nutrition education in school adolescents - Ferreira, Luiza Deutschendorf (2020)
Introduction and objective: The school years are a key period as a target for nutritional interventions to promote healthy lifestyle, so the study aims to evaluate the impact of group nutritional intervention on the nutritional status of adolescent students at an elementary public school in Blumenau. Materials and Methods: This is a longitudinal study, experimental, applied and quantitative approach with a sample of 91 students between 10 and 17 years old of both genders. The adolescents underwent anthropometric assessment in 2017, 2018 and 2019 and participated in 6 Food and Nutrition Education activities in 2018. The comparison between group means was performed by the paired t Student test (before and after periods without and with intervention). The association between qualitative variables was tested with the support of Q-square test. Statistical analyzes adopted p <0.05 Results: During the intervention period, there was an increase in the number of male adolescents with thinness and females with eutrophy, and a reduction in the frequency of overweight and obesity in both genders. On the other hand, there was a reduction in thinness and normal weight and an increase in the number of overweight and obese adolescents. There was no statistical difference in the average anthropometric indicators body mass index / Age and Stature / Age between the beginning and the end of periods without or with nutritional intervention. Conclusion: Despite the lack of statistical difference in the anthropometric evaluation indicators, the activities performed were accompanied by favorable changes in the nutritional status of the evaluated adolescents.